ANALISIS KELAYAKAN USAHATANI TERPADU PADA ZONA AGROEKOSISTEM LAHAN KERING DATARAN TINGGI BERBASIS KONSERVASI - M. Basri; Noldin Abolla; Nimrot E.M Neonufa (Politeknik Pertanian Negeri Kupang, 2018)
This study aims to analyze the feasibility of the integrated farming system in a conservation-based highland and dryland agroecosystem zone between plants and livestock. The method of determining the sample used in the study was random with a sample size of 36 farmers. The data used in this study were collected through observation techniques, interview techniques, and desk study. The data then was examined through (1) analysis of revenues and revenues, and (2). Analysis of business feasibility. The result shows that from the results of economic analysis of integrated farming based on Conservation in Netpala village, North Molo sub-district, Timor Tengah Selatan district (TTS) with an average land area of 1 ha, the total cost needed was Rp. 27,550,000. IDR 84,600,000, and income of IDR 57,050,000 per planting season. With an R / C ratio of 2.07.